Global, regional, and national burden of cardiovascular disease due to dietary risks, 1990–2021 - Yu, Yunfeng; Tan, Danni; Yang, Xinyu; Wu, Jingyi; Hu, Gang; Jian, Weixiong; Wang, Liping (Frontiers in Nutrition, 2025)
ObjectiveThis study investigated the burden and temporal trends of cardiovascular disease due to dietary risk (CVD-DR) from 1990 to 2021.MethodsThis study used the Global Burden of Disease (GBD) 2021 database to calculate the estimated deaths, age-standardized mortality rate (ASMR), disability-adjusted life years (DALYs), age-standardized DALY rate (ASDR), and annual percentage change (EAPC) from CVD-DR from 1990 to 2021. We then compared the ASDRs and ASMRs of CVD-DR according to region, socio-demographic index (SDI), sex, and age group. Finally, we evaluated the burdens of cardiovascular disease (CVD) induced by 13 different dietary risks.ResultsFrom 1990 to 2021, the global DALYs and deaths from CVD-DR increased by 36.5% and 44.8%, respectively, whereas the ASDR and ASMR decreased to 62.9% and 61.4% of the baseline values, respectively. In 2021, 5,833,851 deaths and 134,179,728 DALYs from CVD-DR were reported, with an ASMR of 69.81 per 100,000 population and an ASDR of 1,563.86 per 100,000 population. Hypertensive heart disease (HHD), stroke, and ischemic heart disease (IHD) due to dietary risks were the primary components. Correlation analyses indicated that ASMR and ASDR and their EAPCs were negatively correlated with SDI (ρ < 0, P < 0.05). Among the 13 dietary risk factors, a diet high in sodium, low in fruits, and low in whole grains was the main dietary risk factor for CVD.ConclusionOver the last 31 years, the overall global burden of CVD-DR has increased, whereas the age-standardized burden has decreased, with the burdens mainly originating from IHD, stroke, and HHD. Lower-SDI regions face a higher and faster-growing burden of CVD-DR. Diets high in sodium and low in fruits and whole grains were the leading dietary contributors to this burden.